Low plasma FVII:C and activated FVII as predictive markers for overt disseminated intravascular coagulation - Lertthammakiat, Surapong; Anantasit, Nattachai; Anurathapan, Usanarat; Sirachainan, Nongnuch; Kadegasem, Praguywan; Chuansumrit, Ampaiwan (Thrombosis and Haemostasis, 2017)
In sepsis, binding of factor VII (FVII:C) and activated factor VII (FVIIa) with tissue factor is the key step of coagulation resulting in disseminated intravascular coagulation (DIC). We conducted a prospective cohort study among 47 septic patients, aged 8 months to 18.8 years. They were initially divided into three groups of no DIC (n=27), non-overt DIC (n=14) and overt DIC (n=6). Blood samples were collected at 0, 24 and 48 hours (h) after the onset of sepsis. At the onset of sepsis, FVII:C tended to be lower in the non-overt DIC [median 57% (interquartile range [IQR] 41–80)] and overt DIC groups [33% (23–52)] than that in the no DIC group [65% (44–87)]. Whereas FVIIa tended to be lower in the overt DIC group [1.29% (0.50–4.19)] than those in the non-overt DIC [3.01% (1.01–5.24)] and no DIC groups [2.49% (1.14–3.13)]. At 24 h, FVII:C was significantly lower in the non-overt DIC [57% (41–101)] and overt DIC groups [31% (28–49)] than that in the no DIC group [83% (70–102)]. While FVIIa was significantly lower in the overt DIC group [2.15% (0.86–3.96)] than that in the no DIC group [3.83% (2.90–5.46)]. Using FVII:C <65% or FVIIa <3% at 24 h among patients without hepatic dysfunction to determine overt DIC at 24 h, the sensitivity was 83.9% and 77.4%, respectively, and the specificity was both 83.3%. Patients with low FVII:C and low FVIIa at 24 h after the onset of sepsis had a 20.8-fold (95% confidence interval [CI], 2.0–213.0, p=0.010) and 14.4-fold (95%CI, 1.5–142.4, p=0.023) chance of overt DIC.
Keywords: Activated factor VII; factor VII; sepsis; disseminated intravascular coagulation; paediatric patients